Seksizem v poimenovanjih poklicev? Analiza poklicnih nazivov v slovenskih časopisih in revijah (1958–2018) - Mikić, Jasna (Teorija in praksa, 2025)
The purpose of this paper is to analyse the grammatical forms in which occupational titles appeared and, through the lens of feminist stylistics, to identify aspects of sexism in language. The analysis covers four points in time (1958, 1978, 1998, 2018) and focuses on three newspapers/magazines (Delo, Gospodarski vestnik, Naša žena). The findings indicate that the language was largely subject to sexism, as primarily reflected in the dominant use of the masculine grammatical form as generic and in the gender-specific use of language while referring to occupations. These practices reflect both established linguistic norms and gender stereotypes.
Keywords: gender; jezik; language; occupational titles; occupations; poklici; poklicna poimenovanja; seksistični jezik; seksizem; sexism; sexist language; spol; Študije spolov; Ženske v medijih